How does parental rearing patterns of children in upper primary school impact social withdrawal? A mediating effect of emotional regulation - Yu, Tao; Ma, Zhengyu; Zhang, Yu (Frontiers in Psychology, 2024)
The present study endeavors to elucidate the impact of emotional regulation and parental rearing patterns on the social development of children in the upper grades of primary school. A burgeoning body of literature suggests that these factors significantly influence children's social adaptation and emotional well-being, yet a comprehensive examination of these relationships is warranted.: Employing a cross-sectional design, this investigation utilized the Egna Minnen Beträ ffande Uppfostran (EMBU), Emotional Regulation Questionnaire for Children (ERQC), and Child Behavioural Issues Scale (CBCL) to assess a sample of 276 pupils across grades 4 to 6. The selection of these instruments allowed for a multifaceted evaluation of the constructs of interest. Results: A pronounced disparity in parental rearing practices, emotional regulation capabilities, and levels of social withdrawal was observed among the different grades, with grade 5 exhibiting the most pronounced effects. Parental emotional warmth demonstrated a significant positive correlation with children's emotional regulation abilities, while punitive, rejecting, and preferential behaviors were inversely correlated. The study established that parental rearing practices indirectly influence social withdrawal through the mediating role of children's emotional regulation, underscoring the complexity of this relationship. Conclusion: The results underscore the salient role of parental rearing and emotional regulation in the social development of children. The study contributes to the existing literature by providing a nuanced understanding of the mechanisms through which parenting styles and emotional competencies interplay to affect social withdrawal. Implications for educational practices and future research directions are discussed.